2014
DOI: 10.1038/mt.2014.26
|View full text |Cite
|
Sign up to set email alerts
|

Human Skeletal Muscle–derived CD133+ Cells Form Functional Satellite Cells After Intramuscular Transplantation in Immunodeficient Host Mice

Abstract: Stem cell therapy is a promising strategy for treatment of muscular dystrophies. In addition to muscle fiber formation, reconstitution of functional stem cell pool by donor cells is vital for long-term treatment. We show here that some CD133(+) cells within human muscle are located underneath the basal lamina of muscle fibers, in the position of the muscle satellite cell. Cultured hCD133(+) cells are heterogeneous and multipotent, capable of forming myotubes and reserve satellite cells in vitro. They contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 46 publications
8
66
0
Order By: Relevance
“…However, their kinetics of myogenic differentiation vary significantly than that of SCs, only expressing myogenic markers at the onset of terminal differentiation . In a mouse cryoinjury model, intramuscular transplantation of muscle‐derived CD133+ cells re‐populated the SC niche, and these donor cells were observed to mount a potent regenerative response after subsequent re‐injury …”
Section: Advances In Treatment Of Local Muscle Injuriesmentioning
confidence: 99%
“…However, their kinetics of myogenic differentiation vary significantly than that of SCs, only expressing myogenic markers at the onset of terminal differentiation . In a mouse cryoinjury model, intramuscular transplantation of muscle‐derived CD133+ cells re‐populated the SC niche, and these donor cells were observed to mount a potent regenerative response after subsequent re‐injury …”
Section: Advances In Treatment Of Local Muscle Injuriesmentioning
confidence: 99%
“…The results showed that the CD133 + stem cells outperformed myoblasts in terms of migration, repopulation of the satellite cell niche, and overall regenerative capacity. A recent study demonstrated that human CD133 + cells transplanted into mouse muscles are functional and can give rise to satellite cells in vitro and in vivo . However, similar to myoblasts, the prolonged culture of donor CD133 + cells was shown to reduce their effectiveness in vivo.…”
Section: Stem Cells For Skeletal Muscle Regenerationmentioning
confidence: 99%
“…A recent study demonstrated that human CD133 þ cells transplanted into mouse muscles are functional and can give rise to satellite cells in vitro and in vivo. 121 However, similar to myoblasts, the prolonged culture of donor CD133 þ cells was shown to reduce their effectiveness in vivo. In another study, human adult CD133 þ stem cells were mobilized from the peripheral blood by granulocyte colony-stimulating factor (G-CSF) and intramuscularly injected into lacerated muscles in athymic rats.…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…These authors have isolated muscle-derived CD133+ stem cells from DMD patients and genetically corrected these to express a functional form of dystrophin. The genetically corrected human CD133+ cells were transplanted into immunodeficient dystrophic mice and showed recovery of dystrophin expression, regeneration of muscle fibers and notably, greater in vitro and in vivo measured muscular force output [7880]. …”
Section: Stem Cells and Regenerationmentioning
confidence: 99%